Informationstheoretisches Modell der Carcinogenese - H. Schaltegger (CHIMIA)
The effects of chemical and physical agents on genetic material have been explained by the interaction of the cell with its immediate environment. Another possibility of cancerogenesis stems from the thermodynamic- and information theory-based premise that cancerogens must all act on the genom of a cell with the same code.